A non-invasive human skin sampling technique for the detection of volatile organic compounds associated with Mycobacterium tuberculosis - Rohwer, Egmont Richard (University of Pretoria, 2022)
Dissertation (MSc (Chemistry))--University of Pretoria, 2022.